Burden of late-preterm infant at a tertiary care neonatal intensive care unit - A prospective observational study - Deshabhotla, Saikiran; Hussain, Aafaque; Tandur, Baswaraj (Indian Journal of Child Health, 2018)
Background: Infants born at 340?7 through 366?7 weeks’ gestation are called as “late-preterm” infants. Even though physically resembling infants born at term gestation (370?7–416?7 weeks) they are developmentally immature and are at higher risk of morbidity and mortality. Objective: The objective of the study was to study the etiology and burden of late-preterm infant (340/7–366/7 weeks) birth. Material and Methods: This prospective observational study was conducted over 11 months in a tertiary care Level III neonatal intensive care unit in an urban city of India to elucidate the burden and etiology of late-preterm infant birth. Results: In our study, 17.5% (160, n=916) of total admissions were late-preterm infants. The most common underlying cause of late-preterm infant birth in this cohort was a previous lower segment caesarian section (LSCS) 27.5% (44, n=160) and pregnancy-induced hypertension 25% (40, n=160) followed by preterm labor 15.6% (25, n=160). Median gestation was 35 weeks with IQR (34–36 weeks). The median birth weight was 2100 grams with IQR (1900–2400 g). Conclusion: Late-preterm infants account for a significant proportion of preterm births and major burden on the neonatal intensive care workload. The most common reason of late-preterm births was an elective LSCS, done due to an earlier LSCS delivery.